Analysis of the process of scientific literacy in children in non-formal education spaces and science communication - Scalfi, Graziele (2019)
We understand Science Literacy as a citizens' right and a lifelong process that occurs in different educational spaces. We assume that the child, understood as an active actor, participant and producer of culture, can be considered an agent of science literacy, through the promotion of dialogue between children's cultures and scientific culture. The aim of this paper is, based on the theoretical-methodological framework of Science Literacy Indicators, to analyze the applicability of the tool for the study and evaluation of educational and science communication activities for children. The framework consists of four indicators (Scientific, Social Interface, Institutional and Interaction) and their attributes. In this sense, we present the indicators articulating with aspects of childhood and supported by results of empirical studies to exemplify and discuss their use for analysis of educational actions in non-formal education spaces. Finally, we discuss the role of this framework in the process of evaluation and planning of educational actions and science communication targeted at promoting children's scientific literacy.